Multifunctional Building Design with a Green Architecture Approach in Medan City - Muhammad Abdillah Sm; Dara Wisdianti; Peranita Sagala (INFOKUM, 2026)
The population growth of Medan City, which will reach 2.54 million people in 2024, puts significant pressure on the city's infrastructure needs, especially vertical housing, commercial space, and efficient workspaces. The limited urban land encourages the need for a multifunctional building design approach that is able to integrate several functions in one integrated area. This research aims to design a multifunctional building that combines the functions of shopping malls, apartments, and rental offices by applying a green architecture approach as the main design strategy. The method used is a descriptive-qualitative method through literature study, site analysis. The green architecture approach is applied through the integration of vertical gardens on the façade, lighting and natural ventilation systems, the use of environmentally friendly materials, and efficient water and energy management. The design results show that the integration of the three functions in one 14-story building is able to maximize vertical land use while creating a built environment that is responsive to the tropical climate of Medan City. The façade of the building is designed with a double façade system and a green layer that functions as a solar heat filter as well as an architectural aesthetic element. The conclusion of this study shows that the green architecture approach in multifunctional buildings not only improves environmental quality, but also provides economic and social added value for the urban areas of Medan City.